2016
DOI: 10.1061/(asce)cc.1943-5614.0000582
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of GFRP-RC Exterior Beam–Column Joints with Lateral Beams

Abstract: In the past few years, some experimental investigations have been conducted to verify seismic behaviour of fiber reinforced polymer reinforced concrete (FRP-RC) beam-column joints. Those researches were mainly focused on exterior beam-column joints without lateral beams. However, lateral beams, commonly exist in buildings, can significantly improve seismic performance of the joints. Moreover, the way the longitudinal beam bars are anchored in the joint, either using headed-end or bent bars, was not adequately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Similar to the latter reference, Ghomi and El-Salakawy [12] performed experiments on six full-scale BCJs reinforced internally with GFRP bars and stirrups under seismic loading. The joints had lateral beams on all four sides of the column.…”
Section: Non-corrosive Reinforcement Materials For Concrete Structmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the latter reference, Ghomi and El-Salakawy [12] performed experiments on six full-scale BCJs reinforced internally with GFRP bars and stirrups under seismic loading. The joints had lateral beams on all four sides of the column.…”
Section: Non-corrosive Reinforcement Materials For Concrete Structmentioning
confidence: 99%
“…Numerous researchers have worked on the use of FRP sheets as external reinforcement for confinement, shear, and flexural strengthening [1,2,3,4,5,6]. However, only few researchers have started to work on the concept of using FRP as internal reinforcement for BCJs, which are critical components, and their failure could result in the total collapse of the structures [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was concluded that increasing the beam reinforcement ratio can enhance the ability of the joint to dissipate the seismic energy through utilizing the inelastic behavior of concrete. Ghomi and El-Salakawy [19,20] investigated the seismic behavior of the RC beam-column joints with GFRP reinforcement. It was inferred that the axial load level of the columns greatly affects the earthquake's behavior of the RC beam-column joints with GFRP reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the residual drift ratio of two specimens (G-SL and G-XX joints) at the maximum load. Since the authors did not include the second-phase cyclic load-drift curves of the G-SL and G-XX specimens, the discussers included the residual drift ratios of the other two FRP-RC joints that were experimentally tested by Ghomi and El-Salakawy (2018) for comparison. It should be noted that the additional two joints were tested in two loading phases, similar to the specimens in the reference paper.…”
mentioning
confidence: 99%